Trade Liberalization and Embedded Institutional Reform: Evidence from Chinese Exporters - Khandelwal, Amit K; Schott, Peter K; Wei, Shang-Jin (American Economic Review, 2013)
If trade barriers are managed by inefficient institutions, trade liberalization can lead to greater-than-expected gains. We examine Chinese textile and clothing exports before and after the elimination of externally imposed export quotas. Both the surge in export volume and the decline in export prices following quota removal are driven by net entry. This outcome is inconsistent with a model in which quotas are allocated based on firm productivity, implying misallocation of resources. Removing this misallocation accounts for a substantial share of the overall gain in productivity associated with quota removal. (JEL F13, F14, L67, O14, O19, P23, P33)